Universal host materials for red, green and blue high-efficiency single-layer phosphorescent organic light-emitting diodes. Issue 46 (12th November 2020) - Lucas, Fabien; Quinton, Cassandre; Fall, Sadiara; Heiser, Thomas; Tondelier, Denis; Geffroy, Bernard; Leclerc, Nicolas; Rault-Berthelot, Joëlle; Poriel, Cyril
Abstract : As simplifying the device structure is a key step for the future of organic electronic, we report herein high efficiency universal host materials for red, green and blue Single-Layer Phosphorescent OLEDs. Abstract : Simplifying the structure of Organic Light-Emitting Diodes (OLEDs) has been for the last twenty years the purpose of many studies. However, despite these efforts, only a few materials provide high efficiency devices. We report herein efficient design strategies to construct universal host materials for red, green and blue Single-Layer Phosphorescent OLEDs (SL-PhOLEDs). The three materials investigated, SPA-2, 7-F(POPh2 )2, SPA-3, 6-F(POPh2 )2 and SPA-2-FPOPh2, have been synthesized via an efficient approach and are constructed on the association of an electron rich phenylacridine unit connected by a spiro carbon atom to three different electron-deficient diphenylphosphineoxide-substituted fluorenes. Electrochemical, spectroscopic, thermal and transport properties are discussed. The position (C2 and C7 vs. C3 and C6) and the number (1 vs. 2) of diphenylphosphineoxide units on the fluorene backbone have been particularly studied to highlight the best combination in term of device performance. Red, green and blue SL-PhOLEDs (RGB SL-PhOLEDs) have been fabricated and characterized and their performances discussed. Of particular interest, we managed to reach a FIr6-based SL-PhOLED (with SPA-2-FPOPh2 ) possessing an external quantum efficiency of 9.1% and a low threshold voltage (below 3 V). As far as we know, this is the first example of SL-PhOLED using this blue phosphorescent emitter. On the other hand, with notably a very high external quantum efficiency of 18% with FIrpic as sky blue emitter, SPA-2, 7-F(POPh2 )2 displays the highest overall performance in the series and the highest overall performance ever reported for RGB SL-PhOLEDs using a universal host. This not only shows that the association of phenylacridine and diphenylphosphineoxide units fulfils the required criteria for an universal host for high efficiency SL-PhOLEDs but also highlights that the arrangement of these fragments drives the device performance.